Molecular Characterization of Fungal Colonization on the Provox™ Tracheoesophageal Voice Prosthesis in Post Laryngectomy Patients - Hasti Kamali sarvestani; Roshanak Daie Ghazvini; Syed Jamal Hashemi; Mohsen Geramishoar; Saham Ansari; Zahra Rafat; Aslan Ahmadi; Pedram Borghei; Miad Elahi; Abas Rahmi foroushani; Muhammad Ibrahim Getso; Shima Aboutalebian; et al. (Tehran University of Medical Sciences, 2022)
Background: Tracheoesophageal voice prostheses (TVPs) have been the gold standard in rehabilitation, after laryngectomy, producing faster and premier voicing towards esophageal speech. Fungal colonization shortens the device's lifetime and leads to prosthesis dysfunction, leakage, and subsequent respiratory infection. Therefore, in the current study, we aimed to investigate the fungal colonization patterns and to propose prophylactic measures that shall increase the longevity of voice prosthesis. Methods: Failed TVPs were removed - due to leakage and/or aspiration - from 66 post laryngectomy patients and examined. They were referred to Amiralam and Rasoul Hospital, the main centers of Ear, Nose, and Throat in Tehran, Iran from April 2018 to January 2020. Fungal colonization patterns were assessed using DNA sequencing techniques. Furthermore, the susceptibility to fluconazole, amphotericin B, nystatin, and white vinegar was evaluated according to the Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Resident fungal species from the upper airways colonized all the 66 TVPs (100%). Diabetes (31%) and smoking (98%) were the predominant underlying disease and predisposing factors, respectively. Among the 79 fungal agents isolated from the 66 TVPs, Candida glabrata (n=25, 31.7%) was the most common. A significant reduction in minimum inhibitory concentration (MIC) values were observed for white vinegar when used alone (P<0.05). Conclusion: White vinegar at a very low concentration could decrease the amount of fungal colonization on TVPs without any adverse effects; its wide accessibility and affordability ensure a decrease in the overall health cost.